Whole-body and site specific [18F]FDG uptake patterns on PET/CT have limited value in differentiating between polymyalgia rheumatica and other inflammatory diseases: two cohorts of treatment-naïve suspected polymyalgia rheumatica - Andreas Wiggers Nielsen; Gijs D. van Praagh; Kornelis S. M. van der Geest; Ib Tønder Hansen; Berit Dalsgaard Nielsen; Søren Geill Kjær; Jesper Blegvad-Nissen; Kate Rewers; Christian Møller Sørensen; Elisabeth Brouwer; Ellen-Margrethe Hauge; Lars Christian Gormsen; et al. (EJNMMI Research)
Abstract Background It has been hypothesized that 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG) positron emission tomography (PET) computed tomography (CT) can distinguish polymyalgia rheumatica (PMR) from non-PMR patients based on the [18F]FDG-uptake patterns. Nevertheless, a comprehensive assessment of whole-body [18F]FDG-patterns across all uptaking musculoskeletal sites, as well as site-specific [18F]FDG-uptake patterns, has not been conducted. Therefore, this study aimed to investigate both the overall whole-body [18F]FDG-uptake patterns and the specific uptake patterns at individual sites in patients suspected of having PMR. Methods Two distinct cohorts of patients with suspected PMR from Denmark and the Netherlands were prospectively included, encompassing 66/27 and 36/21 PMR/non-PMR patients, respectively. The cohorts consisted of treatment-naïve patients, who underwent pre-treatment [18F]FDG-PET/CT scans. The [18F]FDG-uptake was then assessed across 34 different anatomical sites. Furthermore, the site-specific [18F]FDG-uptake pattern within each anatomical site was categorized according to its shape. Results Patients with PMR were more likely than non-PMR patients to have bilateral [18F]FDG-uptake equal to or above liver compared at the ischial tuberosities (91%/41%), shoulder joints (86%/45%), hip joints (83%/52%), and along the lumbar spinal processes (70%/30%). However, a subgroup analysis comparing non-PMR patients with other inflammatory conditions to patients with PMR revealed that several non-PMR patients exhibited a similar whole-body [18F]FDG-uptake pattern. Furthermore, site-specific [18F]FDG-uptake patterns were similar in patients with PMR and non-PMR. Conclusion Assessing whole-body or site-specific [18F]FDG-uptake patterns does not improve the diagnostic accuracy in distinguishing PMR from other inflammatory diseases. Consequently, [18F]FDG-PET/CT should mainly be used to rule out a clinical diagnosis of PMR. Trial registration: ClinicalTrials.gov (NCT04519580). Registered 17th of August 2020.